Analisis Jenis Kalimat Berdasarkan Tujuan pada Teks Drama Buku Bahasa dan Bersastra Indonesia Kelas XI Kurikulum Merdeka - Jely Mila Ashari; Monica Zahroh; Ergita Amiarti; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Muhamad Haryanto (Student Research Journal, 2023)
The Indonesian language is the national and state language, but it is also a compulsory subject at all levels of education. The research entitled Analysis Types of Sentences Based on Purpose of Drama Texts in the book of Buku Bahasa dan Bersastra Indonesia Class XI in with Merdeka Curriculum aimed to fulfill a final assignment in the Fundamentals of Syntax lesson, and also to explain purpose-based sentence variations in drama texts on the book of Bahasa dan Bersastra Indonesia with Mereka curriculum. This article uses qualitative methods by researching, describing, and analyzing each type of sentence according to its purpose. The results of the study show that in the three drama texts, there are four types of sentences (1) declarative sentences, (2) interrogative sentences, (3) imperative sentences, and (4) interjective sentences. The drama script Ayahku Pulang by Usmar Ismail found 49 declarative texts, 40 types of interrogative texts, ten imperative texts, and 33 interjective sentences. There are 20 types of sentences in the drama Game Kehidupan by Rahmah Purwahida, consisting of 6 declarative sentences, five interrogative sentences, one imperative sentence, and eight interjective sentences. The drama text Siluet Fajar by Rahmah Purwahida found 25 types of sentences consisting of 7 type of declarative sentences, five types of interrogative sentences, three imperative sentences, and ten interjective sentences. Through this research, it expected that it can help teachers to review lesson plans regarding drama texts, and to assist students in understanding types of sentences based on their purpose in drama texts.